y 2 ( x 2 + y 2 − 2 x y − x − y ) = ( x + y ) 2 ( x − y )
Find the number of integer pairs ( x , y ) that satisfy the above expression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is best to split up the solution into cases of x ≥ y and x < y , instead of progressing the cases in parallel.
For Δ 1 , shouldn't we require k = 2 , 4 instead?
Is it possible to solve it this way?
Let z be the gcd(x, y), x = mz, y = nz, and m and n are coprime. Now we see that
z^4 * n^2 * (m^2 + n^2 - 2mn) = z^3 * m^2 * (m + n)
z * n^2 * (m^2 + n^2 - 2mn) = m^2 * (m + n) if z is not 0
First thing we can notice is that one solution is clear if we set z = 0. Now, since m and n are coprime, n^2 must divide (m + n), but that means n divides m even though they are mutually prime. That means n = 1 and m divides z. We now see that m is divisible by n. If we put x = ym into the equation, we get
y^4 * (m - 1)^2 = m^2 * y^3 * (m+1)
y(m - 1)^2 = (m + 1)m^2
(m - 1)^2/m^2 = (m + 1)/y
On the LHS, (m - 1) and m are coprime, which means that (m + 1) is a multiple of (m - 1)^2 (or vice versa). This is true for two integers m: 2 and 3, the last of which I sadly missed (since (m - 1)^2 = ((m + 1) - 2)^2, (m + 1) has to divide 4, proving 2 and 3 are the only solutions).
So we have two pairs (y, m): (12, 2) and (9, 3). x = my, so the solutions (x, y) are (24, 12), (27, 9) and the previously mentioned (0, 0). My solution seems too simplistic. Am I making any leap of faith logic?
Log in to reply
That's a nice way to make use of n 2 ∣ m + n .
Can you clean it up and I can post it as a separate solution?
First, if
x
=
0
then,
y
2
(
y
2
−
y
)
=
−
y
3
, so
y
=
0
if
y
=
0
then,
0
=
x
3
, so
x
=
0
And (0,0) satisfies the above expression
let x = g a and y = g b ( G C D ( a , b ) = 1 a n d l e t g a b = 0 a n d b > 0 )
then, g 3 b 2 ( g ( a − b ) 2 − ( a + b ) ) = g 3 ( a + b ) 2 ( a − b ) , so we get b 2 ( g ( a − b ) 2 − ( a + b ) ) = ( a + b ) 2 ( a − b )
Because b 2 divides LHS , b 2 divides RHS and G C D ( a , b ) = 1 , g c d ( b 2 , ( a + b ) 2 ) = g c d ( b 2 , ( a − b ) ) = 1
so b 2 = 1 and b = 1
By " b = 1 "
g ( a − 1 ) 2 − ( a + 1 ) = ( a + 1 ) 2 ( a − 1 )
g ( a − 1 ) 2 = ( a + 1 ) a 2
therefore
(
a
=
2
a
n
d
g
=
1
2
o
r
a
=
3
a
n
d
g
=
9
)
,
(
x
,
y
)
=
(
2
4
,
1
2
)
,
(
2
7
,
9
)
(
∵
g
c
d
(
(
a
−
1
)
2
,
a
2
)
=
1
s
o
(
a
−
1
)
2
∣
a
+
1
,
s
o
a
=
2
o
r
a
=
3
)
By above, ( x , y ) = ( 0 , 0 ) , ( 2 4 , 1 2 ) , ( 2 7 , 9 )
The task allows negative numbers, so one has to check b 2 = 1 ⇒ b = ± 1 . Luckily, in this task both cases lead to the same result.
Log in to reply
thx, but b was already defined by a number greater than 0 in 3rd line
Log in to reply
My mistake, I had missed that all sign cases of x , y are already covered by a , g = 0 in line 3, so we may assume b > 0 without loss of generality. I'm sorry about the confusion!
As already given by Sharky Kesa:
y 2 ( x 2 + y 2 − 2 x y − x − y ) y 2 ( x − y ) 2 − y 2 ( x + y ) y 2 ( x − y ) 2 y 2 ( x − y ) 2 = ( x + y ) 2 ( x − y ) = ( x + y ) ( x 2 − y 2 ) = ( x + y ) ( x 2 − y 2 ) + ( x + y ) y 2 = x 2 ( x + y )
We see that x + y must be square.
Substitute a 2 = x + y b = x − y x = 2 a 2 + b y = 2 a 2 − b to get 4 ( a 2 − b ) 2 b 2 ( a 2 − b ) b a 2 b ∓ b a a ∓ 1 = 4 ( a 2 + b ) 2 a 2 = ± ( a 2 + b ) a = b 2 ± a 3 = a b b 2 ± a 3
Case a = 0 or b = 0 : if a = 0 , then b = 0 and inversely. And then x = y = 0 . It is a solution.
Case a , b , x , y = 0 :
We see that b divides a 3 and a divides b 2 , which means that each primes dividing a also divides b and inversely: a = ∏ p i m i , b = ∏ p i n i with m i , n i ≥ 1
Let consider a prime divisor p so that a = p m ⋅ a ′ and b = p n ⋅ b ′ and ( p , a ′ ) = ( p , b ′ ) = 1 . As p doesn't divide the LHS, it doesn't divide the RHS: p m + n ⋅ a ′ b ′ p 2 n ⋅ b ′ 2 ± p 3 m ⋅ a ′ 3 is an integer not divisible by p
If n < m , then p m + n divides p 3 m ⋅ a ′ 3 but not p 2 n ⋅ b ′ 2 , that cannot be an integer.
If 2 m < n , then p m + n divides p 2 n ⋅ b ′ 2 but not p 3 m ⋅ a ′ 3 , that cannot be an integer.
If m < n < 2 m , then p 2 n ⋅ b ′ 2 and p 3 m ⋅ a ′ 3 both have at least a factor p after the division: the RHS would then be divisible by p .
Therefore, n = m or n = 2 m . We can write a = ∏ q i m i ⋅ ∏ r j m j , b = ∏ q i m i ⋅ ∏ r j 2 m j ⟺ a = e ⋅ f and b = e ⋅ f 2 for some integers e , f
Put it again into ( a 2 − b ) b = ± ( a 2 + b ) a to get ( e 2 ⋅ f 2 − e ⋅ f 2 ) e ⋅ f 2 ( e − 1 ) ⋅ f = ± ( e 2 ⋅ f 2 + e ⋅ f 2 ) e ⋅ f = ± ( e + 1 ) f = ± e − 1 e + 1 = ± ( 1 + e − 1 2 ) .
e − 1 divides 2 and thus can only be e − 1 = ± 1 or e − 1 = ± 2 , which gives ( e , f ) = ( 2 , 3 ) , ( 0 , − 1 ) , ( 3 , 2 ) , ( − 1 , 0 ) .
Case e = 2 , f = 3 : a = 6 , b = 1 8 , x = 2 7 , y = 9
Case e = 3 , f = 2 : a = 6 , b = 1 2 , x = 2 4 , y = 1 2
There are three possibilites : ( 0 , 0 ) , ( 2 7 , 9 ) , ( 2 4 , 1 2 )
We begin by simplifying y 2 ( x 2 + y 2 − 2 x y − x − y ) = ( x + y ) 2 ( x − y ) = ( x 2 − y 2 ) ( x + y ) y 2 ( x − y ) 2 − y 2 ( x + y ) = x 2 ( x + y ) − y 2 ( x + y ) y 2 ( x − y ) 2 = x 2 ( x + y ) At this point we break the problem up into 2 cases: x ≥ y and x < y . We tackle x ≥ y first by taking both sides modulus y , which gives 0 ≡ x 2 ( x + y ) ≡ y 3 ( m o d y ) Hence, x = n y , for some integer n . Plugging this into the equation gives y 2 ( y ( n − 1 ) ) 2 = y 4 ( n − 1 ) 2 = n 2 y 2 ( y ( n + 1 ) ) = n 2 y 3 ( n + 1 ) y = ( n − 1 ) 2 ( n + 1 ) n 2 This means that ( n − 1 ) 2 ∣ ( ( n + 1 ) n 2 ) . Since these factors differ by 1 or 2 , these factors should be relatively small (otherwise they cannot divide each other). Checking the possible values reveals that n ∈ { − 1 , 0 , 2 , 3 } which gives y ∈ { 0 , 0 , 1 2 , 9 } , respectively. Since x = n y , this gives the solutions ( x , y ) ∈ { ( 0 , 0 ) , ( 2 4 , 1 2 ) , ( 2 7 , 9 ) } .
Now, if x < y , then taking both sides modulus x gives y 2 ( x − y ) 2 ≡ y 2 ( − y ) 2 ≡ y 4 ≡ 0 ( m o d x ) so y = n x , for some integer n . Plugging this into the equations gives n 2 x 2 ( x ( 1 − n ) ) 2 = x 4 n 2 ( 1 − n ) 2 = x 2 ( x ( 1 + n ) ) = x 3 ( 1 + n ) x = n 2 ( 1 − n ) 2 1 + n This means that n 2 ( 1 − n ) 2 ) ∣ ( 1 + n ) . Since these factors once again differ by 1 or 2 , we find that the only possible value of n is n = − 1 , which gives x = 0 , which was already determined in the previous case.
Hence, the only solutions are ( x , y ) ∈ { ( 0 , 0 ) , ( 2 4 , 1 2 ) , ( 2 7 , 9 ) } , which means our desired answer is 3 .
There may be an error in the fourth equation: 0 ≡ x 2 ( x + y ) ≡ x 3 m o d y .
Another problem is the implication "Hence x = n y [..]" immediately afterwards:
x 3 ≡ 0 m o d y ⇒ x = n y ∣ Counter-example: x = p prime , y = p 3 , x = n y
The same occurs within the case x < y when the implication "so y = n x [..]" is used.
Problem Loading...
Note Loading...
Set Loading...
Note the following
y 2 ( x 2 + y 2 − 2 x y − x − y ) y 2 ( x − y ) 2 − y 2 ( x + y ) y 2 ( x − y ) 2 y 2 ( x − y ) 2 = ( x + y ) 2 ( x − y ) = ( x + y ) ( x 2 − y 2 ) = ( x + y ) ( x 2 − y 2 ) + ( x + y ) y 2 = x 2 ( x + y )
Note that because the LHS is a perfect square, the RHS must also be a perfect square. Thus, x + y is a perfect square. Let x + y = k 2 or k 2 − x = y . (We will first check when x ≥ y )
y 2 ( x − y ) 2 y ( x − y ) ( k 2 − x ) ( 2 x − k 2 ) 2 x 2 − ( 3 k − 1 ) k x + k 4 = x 2 ( x + y ) = k x = k x = 0 ( 1 )
If x ≤ y , then we have
y ( y − x ) ( k 2 − x ) ( k 2 − 2 x ) 2 x 2 − ( 3 k + 1 ) k x + k 4 = k x = k x = 0 ( 2 )
Let Δ 1 be the discriminant of ( 1 ) and Δ 2 be the discriminant of ( 2 ) . We know that both these discriminants have to be perfect squares for us to have integer solutions.
Δ 1 = k 2 ( 3 k − 1 ) 2 − 8 k 4 = k 4 − 6 k 3 + k 2 = k 2 ( ( k − 3 ) 2 − 8 )
The only values of k which satisfy the discriminant being a perfect square are when k = 0 , 6 .
Δ 2 = k 2 ( 3 k + 1 ) 2 − 8 k 4 = k 4 + 6 k 3 + k 2 = k 2 ( ( k + 3 ) 2 − 8 )
The only values of k which satisfy the discriminant being a perfect square are when k = − 6 , 0 .
Thus, k 2 = 0 , 3 6 , which implies x + y = 0 , 3 6 .
If x + y = 0 , x = − y . Substituting, we have
x 2 ( 2 x ) 2 4 x 4 x = 0 = 0 = 0 , y = 0
Thus, ( 0 , 0 ) is a solution in ( x , y ) . If x + y = 3 6 , y = 3 6 − x . If x is greater than or equal to 18,
( 3 6 − x ) 2 ( 2 x − 3 6 ) 2 − 2 x 2 + 1 0 8 x − 1 2 9 6 x 2 − 5 1 x + 6 4 8 ( x − 2 4 ) ( x − 2 7 ) x = 3 6 x 2 = 6 x = 0 = 0 = 2 4 , 2 7
Thus, the solutions ( x , y ) when x is greater than or equal to 18 are ( 2 4 , 1 2 ) and ( 2 7 , 9 ) . If x is less than or equal to 18,
( 3 6 − x ) 2 ( 2 x − 3 6 ) 2 2 x 2 − 1 0 8 x + 1 2 9 6 x 2 − 5 7 x + 6 4 8 = 0 = 3 6 x 2 = 6 x
This quadratic is unfactorable for integers. Thus, the only solutions or ( x , y ) are ( 0 , 0 ) , ( 2 4 , 1 2 ) and ( 2 7 , 9 ) .